2017
DOI: 10.1186/s12964-017-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

NFAT1-regulated IL6 signalling contributes to aggressive phenotypes of glioma

Abstract: BackgroundWe previously demonstrated that the local immune status correlated with the glioma prognosis. Interleukin-6 (IL6) was identified as an important local immune-related risk marker related to unfavourable prognosis. In this study, we further investigated the role and regulation of IL6 signalling in glioma.MethodsThe expression and prognostic value of IL6 and the IL6 receptor (IL6R) were explored in The Cancer Genome Atlas (TCGA) and REMBRANDT databases and clinical samples. Functional effects of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 39 publications
2
98
0
1
Order By: Relevance
“…In a similar way, reactive astrocytes have been observed to secrete IL‐6, a protein able to enhance primary GBM cell invasion in vitro (Chen et al, ; Li et al, ). Indeed, GBM development, aggressiveness, and poor prognosis have been linked to the high expression of IL‐6 (Jiang, Han, Cheng, Wang, & Wu, ; Tchirkov et al, ). Thus, Jiang et al ()) recently observed that the expression of both IL‐6 and IL‐6‐R was directly correlated to the highly aggressive mesenchymal GBM subtype and poor survival.…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar way, reactive astrocytes have been observed to secrete IL‐6, a protein able to enhance primary GBM cell invasion in vitro (Chen et al, ; Li et al, ). Indeed, GBM development, aggressiveness, and poor prognosis have been linked to the high expression of IL‐6 (Jiang, Han, Cheng, Wang, & Wu, ; Tchirkov et al, ). Thus, Jiang et al ()) recently observed that the expression of both IL‐6 and IL‐6‐R was directly correlated to the highly aggressive mesenchymal GBM subtype and poor survival.…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 99%
“…Indeed, GBM development, aggressiveness, and poor prognosis have been linked to the high expression of IL‐6 (Jiang, Han, Cheng, Wang, & Wu, ; Tchirkov et al, ). Thus, Jiang et al ()) recently observed that the expression of both IL‐6 and IL‐6‐R was directly correlated to the highly aggressive mesenchymal GBM subtype and poor survival. In the same way, Li et al ()) showed that IL‐6 promotes the in vitro invasion of U87 GBM cells by upregulating the expression and secretion of MMP2 and fascin‐1 , an actin‐bundling protein involved in the formation of cellular protrusions enabling cell migration.…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer stem cell nature of isolated GSCs was confirmed by functional assays of self-renewal and tumor formation. The expression of stem cell markers (CD15, CD133, CD44, and Nestin) was detected by flow cytometry or immunofluorescence and the multi-lineage differentiation capacity of GSCs was examined by immunofluorescence (17). In some experiments, GSCs were cultured in DMEM/F12 supplemented with 10% FBS for differentiation.…”
Section: Cell Culture and Gscs Isolationmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described (14,17). Antibodies against CD44 (1:500; ab157107), CD133 (1:100; ab19898), Nestin (1:250; ab6320, ab134017), GFAP (1:1,000; ab7260), b III tubulin (1:1,000; ab78078), NFAT1 (1:200; ab2722), and NDEL1 (1:500; ab25959) were used to detect the expression and intracellular localization of these proteins.…”
Section: Immunofluorescencementioning
confidence: 99%